(untitled) (Eurasian Medical Research Periodical, 2023)
Medical management of rheumatoid arthritis (RA) is aimed at controlling or reducing the inflammatory process in order to prevent or slow down damage to the joint and to maintain or improve the functional status. However, it is well established that inflammation indicators may be stable or improved, whereas radiographic evidence shows that joint damage progresses. A new class of agents termed "biological agents" have been approved for use in RA according to the data of the evidence-based medicine. Until more is known about the long-term safety and efficacy of these drugs, they should be reserved for patients with severe conditions who are progressing despite adequate doses of methotrexate or other DMARDs.